PSIKOLOGI TOKOH DALAM NOVEL WARISAN MASA SILAM KARYA V. LESTARI: TINJAUAN PSIKOLOGI SASTRA - Mualipah; Sukarismanti; Najamudin (MANTRA: Jurnal Sastra Indonesia (Sastra, Bahasa, Budaya), 2023)
V. Lestari is an author who has a different genre from most writers at that time. V. Lestari is more inclined to specialize in writing criminal-detective stories, which is a type of story that requires special care and expertise to compose. And what is even more distinctive is that all of his novels feature the main female character as a detective. The Legacy of the Past Novel is one of the works written by V. Lestari. This novel tells about a boy who is still in elementary school named Kiki. This research examines the psychological elements as an approach because this approach emphasizes more on research on the psychological elements and psychological conditions of the characters. The psychological conditions experienced by the characters in the novel Inheritance of the Silam by V. Lestari are analyzed based on Sigmund Freud's personality theory through Id, Ego and Super Ego. The results of this study are, the personality structure of the main character Kiki and David's subordinate character is dominated by primary processes (imagining and imagining), the ego personality structure of the main character Kiki and David's subordinate character due to encouragement from Id (because ego is the executive or executor), and the structure Superego personality of Linda's subordinate character is dominated by condition and trauma, excessive fear.